2018
DOI: 10.1177/2325957417752260
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Tenofovir Disoproxil Fumarate/Emtricitabine/Elvitegravir/Cobicistat Plus Darunavir Once Daily in Antiretroviral-Naive and Treatment-Experienced Patients: A Retrospective Review

Abstract: Background: : Patients with drug-resistant HIV often require complex antiretroviral regimens. However, combining fixed-dose combination tablets such as tenofovir-disoproxil-fumarate, emtricitabine, and cobicistat-boosted elvitegravir (TDF/FTC/EVG/ cobi) with darunavir (DRV) can provide a simple, once-daily (QD), 2-tablet regimen for patients with drug-resistant HIV. Primary objective was to determine the percentage of patients with HIV-1 RNA <40 copies/mL at 48 weeks. Methods: We performed a retrospective char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Regarding real-world data, the evidence for the effectiveness of this regimen is very limited: only three cohort studies have been published analysing EVG/COB/TDF/ FTC + DRV, all from single centres, involving a very low number of patients, and analysing different endpoints. The effectiveness was high in the three studies: Naccarato et al evaluated 21 treatment-experienced patients (29% of which were virologically suppressed before the switch) who received EVG/COB/TDF/FTC + DRV: at week 48, 14 (67%) patients had undetectable viral load, 1 had virologic failure (> 40 copies/ml) and 6 had stopped the treatment or had no viral load data [5]. Harris et al evaluated the simplification to the same regimen in 10 virologically suppressed patients: 8 of them had viral loads < 40 copies/ml at weeks 24 and 48 and all of them had viral loads < 200 copies/ml up to week 48 [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding real-world data, the evidence for the effectiveness of this regimen is very limited: only three cohort studies have been published analysing EVG/COB/TDF/ FTC + DRV, all from single centres, involving a very low number of patients, and analysing different endpoints. The effectiveness was high in the three studies: Naccarato et al evaluated 21 treatment-experienced patients (29% of which were virologically suppressed before the switch) who received EVG/COB/TDF/FTC + DRV: at week 48, 14 (67%) patients had undetectable viral load, 1 had virologic failure (> 40 copies/ml) and 6 had stopped the treatment or had no viral load data [5]. Harris et al evaluated the simplification to the same regimen in 10 virologically suppressed patients: 8 of them had viral loads < 40 copies/ml at weeks 24 and 48 and all of them had viral loads < 200 copies/ml up to week 48 [6].…”
Section: Discussionmentioning
confidence: 99%
“…4 Centro Nacional de Epidemiología, Instituto de Salud Carlos III, Madrid, Spain. 5 Hospital Universitario Ramón y Cajal, Madrid, Spain. 6 Corporació Sanitària Parc Taulí, Barcelona, Spain.…”
Section: Abbreviationsunclassified
See 2 more Smart Citations
“…It possesses potent inhibitory activity with an IC 50 of 7.2 nM in the ST assay, and shows an EC 50 of 0.9 nM in an acute HIV-1 infection assay [ 66 , 67 ]. Clinical trials showed that the Genvoya regime was very effective in reducing viral load (plasma HIV-1 RNA levels) to less than 40 copies/ml at the week 48 assessment, and displayed durable suppression of viral load to less than 50 copies/ml for up to 6 months [ 68 ]. The discovery of EVG and the development of Genvoya brought in an important advance with once-daily single-tablet regime for the effective treatment of HIV-1 infection.…”
Section: Inis Approved For Clinical Applicationmentioning
confidence: 99%